Tablighi Jamaat, An Islamic Revivalist Movement and Radicalism Issues - Sukron Mamun (Islam Realitas: Journal of Islamic and Social Studies, 2019)
This article discusses Tablighi Jamaat as Islamic transnational movement that emerged in the early 20th century and attracted a great attention post nine eleven in America. One of the interesting that invite debate among scholars is that Tablighi Jamaat is a part of radicalist movements or terrorist groups or only an Islamic missionary movement. Those debates are related to the existence of Tablighi Jamaat around the world. Moreover, it can be said that every country in the world have settled by Tablighi Jamaat. American Foreign Council report shows that tablighist is estimated 50 to 80 million people. The numbers have invited suspicion of policy maker from many countries, particularly on radicalism issues. Discussion on this article based on basic questions on who are Tablighists, their aims and their activities. However, the main purpose of this article to show how scholars argue on the existence of Tablighi and possibility on Tablighi Jamaat involvement on radicalism actions. This study based on library research and direct observation on Tablighi in Central Java dan East Java.Artikel ini mendiskusikan Tablighi Jamaat sebagai gerakan Islam transnasional yang muncul pada awal abad ke-20 dan menyita perhatian setelah peristiwa nine eleven (9/11) di Amerikan. Salah satu hal yang menarik dan mengundang perdebatan di kalangan ilmuwan adalah apakah Tablighi Jamaat merupakan bagian dari gerakan atau kelompok radikalis atau bahkan teroris, atau sebatas gerakan keagamaan belaka. Perdebatan-perdebatan tersebut terkait dengan keberadaan Tablighi Jamaat di berbagai Negara di seluruh dunia. Bahkan, dapat dikatakan bahwa setiap Negara telah terjamah oleh keberadaan Tablighi Jamaat. Dewan Amerika Luar Negeri menunjukkan bahwa diperkirakan ada 50 hingga 80 juta tablighis di seluruh dunia. Jumlah tersebut tentu mengundang kekhawatiran para pengambil kebijakan di berbagai negera, khususnya terkait dengan isu radikalisme. Diskusi dalam artikel ini berdasarkan pada pertanyaan-pertanyaan mendasar siapa sebenarnya Tablighi Jamaat, tujuan dan aktivitas mereka. Namun, tujuan utama dari artikel ini adalah untuk menunjukkan argument-argumen para ilmuwan mengenai keberadaan Tablighi Jamaat dan kemungkinan Tablighi Jamaat terlibat dalam aksi-aksi radikalisme. Kajian ini didasarkan pada kajian kepustakaan dan obersevasi langsung penulis, khusunya di wilayah Jawa Tengah dan Jawa Timur